Searching for ’real’ Hottentots: the Khoekhoe in the history of South African physical anthropology - Morris, A. (Southern African Humanities, 2021)
Physical anthropology was obessed with types and racial purity for an exceptionally long time, only breaking through the clouds of typology in the 1960s and 1970s. For at least a hundred years, research on the Khoekhoe peoples of southern Africa was directed by the idea of Hamitic origins for these pastoralists, and the dynamics and variation of the native populations were ignored so that individuals that fit the pre-conceived appearance of the mythical Hamite could be identified. The three-race model (Bushman, Hottentot and Bantu) held sway until Singer’s 1958 publication of The Boskop ’race’ problem in which he criticized the type concept. Only after that seminal paper did population models begin to be considered in the study of aboriginal populations in South Africa. Here, I examine the important philosophical shift from ’types’ to ’populations’ in our understanding of the physical anthropology of the Khoekhoe. For many new researchers in the field, the earlier literature must seem exceptionally alien with all its talk of types, bloodlines and physical features treated as if they were genetic alleles. How much information from the earlier studies can be salvaged?